Elemen Pembentuk Citra Kawasan Bersejarah Di Pusat Kota Malang - Pettricia, Hana Ayu; Wardhani, Dian Kusuma; Antariksa, Antariksa (RUAS, 2014)
The study of the image of an area needs to be done to find out the identity of the place. District of Klojen is an area that has a legacy of historic buildings and environment in the Dutch colonial era, therefore it is necessary to study the image of the District Klojen kawasan bersejarah.This study aims: (1) analyze the imageforming elements in the historic district based on the perception of residents Klojen District of Malang, and (2) analyze the factors that influence respondents in identifying the image-forming elements in the historic district Klojen. Malang resident perception is divided into three groups, ie community groups, students, and experts. The method are used descriptive analytical and evaluative analysis. Descriptive methods isused to analyze the elements of the image forming region, using mental maps and interviews. Evaluative analysis used to analyze the factors that influence respondents to identify the image of the historic district, and to review the typology of perception of the respondents use the gestalt theory. The results are (1) image of the historic downtown district that is Klojen still can’t properly captured by the inhabitants of the city of Malang, and the District Klojen still highlight the historic image, (2) factors that influence respondents' perceptions are internal factors and external. Typology of perception, internal factors and external factors had ties in identifying the image of the historic district.Key words: image, historic, gestalt theory, mental maps.